Glucose Metabolism in Cancer and Ischemia: Possible Therapeutic Consequences of the Warburg Effect. (17th February 2017) - Salamon, Spela; Podbregar, Eva; Kubatka, Peter; Büsselberg, Dietrich; Caprnda, Martin; Opatrilova, Radka; Valentova, Vanda; Adamek, Mariusz; Kruzliak, Peter; Podbregar, Matej
ABSTRACT: The Warburg effect states that the main source of energy for cancer cells is not aerobic respiration, but glycolysis—even in normoxia. The shift from one to the other is governed by mutually counteracting enzymes: pyruvate dehydrogenase and pyruvate dehydrogenase kinase (PDK). Anaerobic metabolism of cancer cells promotes cell proliferation, local tissue immunosuppression, resistance to hypoxic conditions, and metastatic processes. By switching glucose back to oxidative metabolism, these effects might be reversed. This can be achieved using PDK inhibitors, such as dichloroacetate. Patients suffering from ischemic conditions might benefit from this effect. On the other hand, the β-blockers (adrenergic β-antagonists) often used in these patients appear to improve cancer-specific survival, and nonselective β-blockers have been shown to promote glucose oxidation. Might there be a link?